Design and build an Employee Performance Assessment Information System Using the Management By Objectivies Method - Oki Sefiana; Sharyanto; Alexius Ulan Bani (Journal of Engineering, Technology and Computing (JETCom), 2022)
PT. Bank Mandiri (Persero) Tbk, which is a State-Owned Enterprise (BUMN) in the banking sector. The current employee performance appraisal information system is still being processed semi-manually using the Microsoft Excel application, so it takes a long time to browse the data and the use of sheet space is too wide. So it is necessary to develop a system in order to create a system that is faster, more precise and accurate using web-based applications. In this study, the authors used several methods, namely observation, interviews and literature study. The data obtained is then described in the form of UML (Unified Modeling Language) and uses the PHP programming language and MySQL as the database. This employee performance appraisal information system will be tested using the Blackbox Testing method. The final result of writing this thesis is the formation of a system procedure using the UML program which describes the current system analysis and the proposed system design. In addition, the authors hope that the design of this new web-based application can shorten the process of evaluating employee performance precisely and accurately.